EFEKTIVITAS MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS IV SD - Syerina Aprilia; Ragil Dian Purnama Putri (Universitas Tribhuwana Tunggadewi, 2026)
The reading comprehension ability of students is still relatively low which can be seen from the difficulty of students in determining the main idea of the text. So that the understanding of the content of the reading is less than optimal. The learning process of grade IV of Muhammadiyah Kadisoka Elementary School in Indonesian language lessons is still teacher-centered where the learning model used is still conventional. The purpose of this study is to determine the effectiveness of the cooperative integrated reading and composition (CIRC) model on the reading comprehension ability of grade IV students. This type of research is quantitative research. The research design used is a non-equivalent control group design. The population of this study was grade IV students of Muhammadiyah Kadisoka Elementary School consisting of three classes totaling 89 people. The sample in this study was taken using a random sampling technique, namely grade IV students as the experimental group totaling 29 people and grade IV students as the control group totaling 29 people. The independent variable used is the use of the CIRC learning model and the dependent variable used is reading comprehension. Data collection techniques consist of observation and tests. The results of the study can be seen from the results of the calculation of the hypothesis test using the independent sample t-test obtained a Sig. value. (2-tailed) is smaller, meaning Ha is accepted and Ho is rejected. Therefore, it can be concluded that the CIRC learning model is effective in improving the reading comprehensio.